Jack Kirby : pencils and inks, artisan edition - Kirby, Jack; Royer, Mike; DC Comics, Inc.; Jack Kirby Museum (San Diego, CA : IDW Publishing, 2016)
An archival project completed in conjunction with DC Comics and with the full cooperation of the Jack Kirby Museum, this volume presents three Kirby first issues as side-by-side examples both in pencil and ink. Includes biographical information.
The Demon #1 -- Kamandi #1 -- Kamandi #1 -- Jack Kirby gallery section.
"Originally published [in the early 1970s by DC Comics] in single magazine form in The Demon #1, Kamandi #1, and OMAC #1"--Title page verso.
Keywords: Kirby, Jack -- Exhibitions